Assessment of interradicular space of the posterior palatal alveolar process for orthodontic mini-implant in different facial morphological pattern - a prospective study. - Singh, Sawan; Balani, Rajesh Kumar; Kallury, Amitabh; Agarwal, Akshay; Gyamlani, Lokesh; Lata, Surabhi (Journal of Neonatal Surgery, 2025)
Background:Orthodontic mini-implants, commonly referred to as temporary anchorage devices, provide reliable skeletal anchorage and have become an important component of contemporary orthodontic treatment. Successful placement of these devices requires adequate interradicular space and sufficient cortical bone thickness to avoid root injury and ensure primary stability. Cone-beam computed tomography allows precise three-dimensional evaluation of alveolar bone morphology and has become a valuable tool for identifying safe insertion sites for orthodontic mini-implants. Objective:To evaluate the interradicular distance and the distance from the palatal cortical bone surface to the narrowest interradicular space in the posterior palatal alveolar process between the maxillary second premolar and 1st molars among individuals with different facial growth patterns using CBCT imaging. Materials and Methods:This retrospective CBCT-based study analysed images obtained from individuals categorized according to facial growth patterns. Measurements of interradicular distance and the distance from the palatal cortical bone surface to the narrowest interradicular space were recorded at multiple vertical levels from the cemento-enamel junction in the posterior palatal interdental region between the maxillary second premolar and 1st molars. Statistical analysis was performed to evaluate variations among different vertical levels and facial growth patterns. Results:Both interradicular distance and the distance from the palatal cortical bone surface to the narrowest interradicular space increased progressively with increasing distance from the CEJ. The region located approximately 6–8 mm apical to the CEJ demonstrated the greatest interradicular space and cortical bone engagement, indicating favourable anatomical conditions for orthodontic mini-implant placement. Conclusion:The posterior palatal interdental region between the maxillary 2nd premolar and 1st molars at approximately 6–8 mm apical to the CEJ represents the most favourable site for orthodontic mini-implant placement. Preoperative CBCT evaluation is recommended to accurately assess interdental bone morphology and identify safe insertion zones, thereby minimising the risk of root proximity and improving the stability of temporary anchorage devices